2020
DOI: 10.1089/thy.2020.0038
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Quality-of-Life Outcome Measures in the Thyroid Cancer Population

Abstract: Background: There is an escalating worldwide population of thyroid cancer (TC) survivors. In addition to conventional metrics of quality of care, quality-of-life (QoL) assessment in TC patients is imperative. TC survivors face unique impediments to health-related quality of life (HRQoL), including thyroid-specific symptoms and exposure to disease-related stressors-including fear of recurrence and financial toxicity-over a prolonged survival period. Survey instruments currently used to assess HRQoL in TC surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 54 publications
(91 reference statements)
1
23
0
1
Order By: Relevance
“…A new finding obtained from this study was that the anxiety and depression scores were significantly higher in the nonadherent group, advocating previous results indicating emotional stress as an important factor determining LT4 adherence 32 . A recently published study revealed that health‐related quality of life in patients with thyroid cancer was negatively influenced by impaired psychological and emotional well‐being due to anxiety, depression, and fatigue 33 . Roberts et al reported that DTC survivors, even those with normal TSH levels and euthyroid state felt that they had missing or inadequate knowledge of lifestyle factors affecting recurrence, negative consequences, symptoms of recurrence, and importance and side effects of medication 34 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A new finding obtained from this study was that the anxiety and depression scores were significantly higher in the nonadherent group, advocating previous results indicating emotional stress as an important factor determining LT4 adherence 32 . A recently published study revealed that health‐related quality of life in patients with thyroid cancer was negatively influenced by impaired psychological and emotional well‐being due to anxiety, depression, and fatigue 33 . Roberts et al reported that DTC survivors, even those with normal TSH levels and euthyroid state felt that they had missing or inadequate knowledge of lifestyle factors affecting recurrence, negative consequences, symptoms of recurrence, and importance and side effects of medication 34 .…”
Section: Discussionsupporting
confidence: 83%
“…32 A recently published study revealed that health-related quality of life in patients with thyroid cancer was negatively influenced by impaired psychological and emotional well-being due to anxiety, depression, and fatigue. 33 Roberts et al reported that DTC survivors, even those with normal TSH levels and euthyroid state felt that they had missing or inadequate knowledge of lifestyle factors affecting recurrence, negative consequences, symptoms of recurrence, and importance and side effects of medication. 34 Disease-free patients with a history of DTC treated with TSH-suppressive doses of LT4 often experience potential psychological adverse effects of thyroid hormone excess, and consequently show poor compliance with their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that patients' lives gradually return to normal after surgery. However, our results are novel in that patient mental health symptoms worsened again 1 year after surgery; this unanticipated result could stem from an increase in fear of recurrence after 1 year had elapsed (40)(41)(42).…”
Section: Discussionmentioning
confidence: 78%
“…In addition to demonstrating the variability in measurement of HR QoL in thyroid cancer patients, this article (2) illuminates several key areas for further study. Anxiety, depression, and fatigue have been cited in multiple studies reviewed as contributors to poor HR QoL in thyroid cancer survivors (2). Given that fatigue and mood problems have also been reported in surveyed patients taking thyroid hormone replacement for hypothyroidism (3), it remains unclear whether these symptoms may be related to thyroid cancer or thyroid hormone replacement.…”
Section: Commentarymentioning
confidence: 99%